Ko-Kreasi Pegiat Seni-Budaya dan Akademisi Berbasis Sains-Khalayak dalam Penyusunan Peta Digital Warisan Budaya di Kecamatan Singosari, Malang: Co-creation between Arts-Culture Artists and Academics in the Citizen Science-Based Development of a Digital Cultural Heritage Map in Singosari District, Malang - Suyadnya, I Wayan; Tirtayani, Luh Ayu; Azhar, Baharuddin; Athoillah, Muhammad Haidar Sabid; Pratama, Axl Ananda Rizky; Sanjaya, Kresnawan Restu; Febriyanti, Annisa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Malang Regency is a prominent tourist destination in East Java, with its appeal focused mainly on historical and cultural heritage tourism. As the site of an early civilization in the archipelago, Malang Regency possesses a diverse collection of tangible and intangible cultural heritage assets, encompassing physical sites, traditions, and performing arts. Notwithstanding this richness, the documentation of these artifacts and assets remains suboptimal. The primary objective of this community engagement activity was to empower local art and culture activists to preserve and promote their cultural assets through the application of digital technology. The methodology employed a participatory approach, in which the local community and academics co-created the collection, location mapping (geotagging), and detailed data verification of cultural sites. The study results demonstrate that utilizing a digital map significantly enhanced public awareness and community involvement in cultural conservation, while also providing an easily accessible platform for tourists and researchers. The study’s conclusion underscores the critical importance of collaboration between digital technology and local wisdom to effectively support community-level cultural heritage preservation. This service project represents the initial phase of a collaborative work process involving the Malang Regency Tourism and Culture Office, cultural activists, and Universitas Brawijaya.